Regularization of autoencoders for bank client profiling based on financial transactions - Andrey Filchenkov; Natalia Khanzhina; Arina Tsai; Ivan Smetannikov (Risks, 2021)
Predicting if a client is worth giving a loan-credit scoring-is one of the most essential and popular problems in banking. Predictive models for this goal are built on the assumption that there is a dependency between the client's profile before the loan approval and their future behavior. However, circumstances that cause changes in the client's behavior may not depend on their will and cannot be predicted by their profile. Such clients may be considered "noisy" as their eventual belonging to the defaulters class results rather from random factors than from some predictable rules. Excluding such clients from the dataset may be helpful in building more accurate predictive models. In this paper, we report on primary results on testing the hypothesis that a client can become a defaulter in two scenarios: intentionally and unintentionally. We verify our hypothesis applying data driven regularized classification using an autoencoder to client profiles. To model an intention as a hidden variable, we propose an especially designed regularizer for the autoencoder. The regularizer aims to obtain a representation of defaulters that includes a cluster of intentional defaulters and unintentional defaulters as outliers. The outliers were detected by our model and excluded from the dataset. This improved the credit scoring model and confirmed our hypothesis.
Keywords: 330; autoencoder; clustering; credit scoring; defaulters; machine learning; neural networks; regularization; transaction profiling